Bhokasi Making Training in Hulawa Village, Buntulia District, Pohuwato Regency - Ria Megasari; Asmuliani R; Muh. Arsyad; Irwan Nooyoo; M. Darmawan (Fakultas Sains Dan Teknologi, Universitas Muhammadiyah Sidenreng Rappang, 2025)
This community service activity was carried out in Hulawa Village with the aim of increasing community knowledge and skills in making bokashi organic fertilizer as an environmentally friendly and economical alternative fertilizer. The problems faced by the local community are the low utilization of organic waste and dependence on chemical fertilizers which have an impact on soil fertility degradation. The activity methods used include counseling, technical demonstrations, and direct practice by participants. This training involved 30 participants from various village communities, utilizing local materials such as straw, bran, livestock manure, and local microorganism solutions (MOL). The results of the activity showed a significant increase in participants' understanding of the benefits of bokashi and their technical skills in producing it. This activity shows that practice-based training with a participatory approach is effective in building village community independence in managing organic fertilizer.